Investigation of integer-coefficient partial response coding in STBC-OFDM system - Syed-Yusof, Sharifah Kamilah; Fisal, Norsheila; Muladi, Muladi (2005)
The carrier-to-interference power ratio in a spacetime block coded (STBC) Orthogonal Frequency Division multiplexing (OFDM) system using the partial response coding approach is investigated. In this paper, the integer polynomial partial response coefficients are implemented. At frequency offset of 0.2, this method enhances the carrier-to-interference power ratio (CIR) by between 0.8 dB to 7.3 dB when the length of polynomial is 3 and 2 respectively. It also effectively reduces the error floor caused by Doppler frequency offset.